Continuous Dry Bulk Density Evaluation Using Borehole Magnetic Resonance and Density Measurements. Issue 1 (1st December 2018) - Hopper, Tim; Neville, Tom; Birt, Benjamin
Abstract : Dry bulk density is a key parameter in resource estimation and mine and process planning. Ore bodies are mapped as volumes, whereas mineralisation grade is reported as mass fractions, requiring rock density to complete the reserves calculation. Similarly, although a volume of rock is to be excavated, planning for the transport and processing of this material takes place in terms of the mass of ore to be handled, again requiring rock density information to convert between the two. Although many different densities can be defined based on the underlying mass and volume definitions, the one of most interest to the mining industry is dry bulk density, or the dry mass per unit volume of in-situ rock. This contrasts with the in-situ bulk density, which includes the mass of any fluids in the pore space of the rock. In-situ bulk density can be accurately measured using borehole geophysical techniques, but no direct downhole measurement of dry bulk density is possible. Therefore, common practice is to determine mass, after drying, and volume of core samples for calculation of dry bulk density. However, this process can be time consuming and problematic with porous or unconsolidated samples. Another approach to estimate dry bulk density, amenable to downhole application and therefore avoiding many of the complications related to core measurements, utilises in-situ bulk density and magnetic resonance porosity measurements.Combining these two measurements allows for continuous dry bulk density evaluation without the need for coring.